(untitled) (Cardiovascular Journal, 2019)
Background: In the diagnosis of acute coronary syndrome, cardiac troponin I is highly reliable and widely available biomarker. Serum level of cardiac troponin I is related to amount of myocardial damage and also closely relates to infarct size. Our aim of the study is to find out the relationship between cardiac troponin I and left ventricular systolic function after acute coronary syndrome. Methods: Total of 132 acute coronary syndrome patients were included in this study after admission in coronary care unit of Sir Salimullah Medical College, Mitford Hospital. Troponin I level was measured at admission and left ventricular ejection fraction (LVEF) was measured by echocardiography between 12-48 hours of onset of chest pain. Results: There was negative correlation between Troponin I at 12 to 48 hours of chest pain with LVEF in these study patients. With a cutoff value of troponin I e”6.8 ng/ml in STEMI patients there is a significant negative relation between 12 to 48 hrs troponin I and LVEF (p<0.001). Sensitivity of troponin I e” 6.8 ng/ml between 12 to 48 hours of chest pain in predicting LVEF <50% in STEMI was 93.75% and specificity was 77.78%. In NSTEMI sensitivity of troponin I e” 4.5 ng/ml between 12 to 48 hours of chest pain in predicting LVEF <50% was 65% and specificity was 54.05%. Conclusion: Serum troponin I level had a strong negative correlation with left ventricular ejection fraction after acute coronary syndrome and hence can be used to predict the LVEF in this setting. Cardiovasc. j. 2019; 12(1): 24-29